Catalitic effect of Co on hydrogen desorption form nanostucturated magnesium hydride - Matović Ljiljana Lj.; Milovanović Snežana S.; Drvendžija Milica M.; Grbović-Novaković Jasmina D. (Hemijska Industrija, 2008)
To study the influence of 3d transition metal addition on desorption kinetics of MgH2 ball milling of MgH2-Co blends was performed under Ar. Microstructural and morphological characterization, performed by XRD and SEM, show a huge correlation with thermal stability and hydrogen desorption properties investigated by DSC. A complex desorption behavior is correlated with the dispersion of the metal additive particles on hydride matrix. The activation energy for H2 desorption from MgH2-Co composite was calculated from both non-isothermal and isothermal methods to be 130 kJ/mol which means that mutually diffusion and nucleation and growth of new phase control the dehydration process.